Problems and Prospects of Backwater Tourism in Kerala with Special Reference to Alappuzha District - Varughese, Ashish (Indian Journal of Marketing, 2013)
The desire to travel in order to see new sights, to gain new experiences, and to live under different environments will always grow. This means that the demand for travel and tourism products will grow, and it can be marketed. The backwaters of Kerala are formed by 40 rivers that flow into the Arabian Sea from the Western Ghats. They are used for the transportation of people and products between villages as well as towns. Today, they play a new role; the backwater tourism is one of the most important tourist products of Kerala. Cruising along the backwaters of Kerala in a houseboat is an enchanting experience for the tourists. In the whole world, similar type of tourism can be experienced in Netherlands only. This paper analyses the marketing activities, the various problems faced by tourism service providers and the perception of tourists towards backwater tourism in Kerala with the help of primary data. The analysis by using Garrett’s ranking shows that parking of boats, unhealthy competition and lack of Government support were the first three main problems faced by the houseboat operators. Tourist’s satisfaction with the main elements of tourism products was measured by using Likert’s five point rating scale. A majority of the tourists were satisfied with backwater tourism and were dissatisfied with the lack of cleanliness of backwaters and hygiene factors.